Growth hormone co-treatment in IVF/ICSI cycles in poor responders - Ob'edkova, Ksenia; Kogan, Igor; Krikheli, Inna; Dzhemlikhanova, Lyailya; Muller, Valeria; Mekina, Irina; Lesik, Elena; Komarova, Evgenia; Mazilina, Maria; Niauri, Dariko; Gzgzyan, Alexandr; Aylamazyan, Edward (Gynecological endocrinology, 2017)
To estimate the efficacy of growth hormone (GH) co-treatment within an antagonist protocol in IVF/ICSI cycles in poor responders. A prospective observational study involving 50 patients underwent a standard antagonist protocol with or without GH co-treatment. GH was administered by a daily subcutaneous injection of 1,33 mg (equivalent to 4 IU) starting from day 1 of ovarian stimulation until the day of 10,000 human chorionic gonadotropin (hCG) triggering . Concentrations of GH, insulin-like growth factor I (IGF-I) and IGF binding protein-3 (IGFBP-3) in serum and follicular fluid were the subject matter of analysis. The GH co-treatment significantly lowered the effective dose of gonadotropins, duration of stimulation, IGFBP-3 level in serum and follicular fluid on the day of oocyte retrieval. The total number of oocytes as well as the number of metaphase II stage (MII) oocytes, two pronucleus (2 pn) zygotes, good-quality transferred embryos was significantly higher in the GH + group. Pregnancy was achieved in patients GH + group only. Positive correlation was found between IGF-I level in follicular fluid, dynamics of IGFBP-3 level changes during stimulation protocol and the number of good-quality transferred embryos in the GH + group. GH administration in IVF/ICSI cycles for poor responders raises ovarian sensitivity to the gonadotropin exogenous influence, increasing number of high-quality embryos and the probability of pregnancy.